2010
DOI: 10.1105/tpc.110.075242
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsisNitrate Transporter NRT1.8 Functions in Nitrate Removal from the Xylem Sap and Mediates Cadmium Tolerance  

Abstract: Long-distance transport of nitrate requires xylem loading and unloading, a successive process that determines nitrate distribution and subsequent assimilation efficiency. Here, we report the functional characterization of NRT1.8, a member of the nitrate transporter (NRT1) family in Arabidopsis thaliana. NRT1.8 is upregulated by nitrate. Histochemical analysis using promoter-β-glucuronidase fusions, as well as in situ hybridization, showed that NRT1.8 is expressed predominantly in xylem parenchyma cells within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
389
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 382 publications
(431 citation statements)
references
References 59 publications
19
389
1
8
Order By: Relevance
“…Both AtNRT1.5 and AtNRT1.8 were shown to be involved in long-distance transport of NO 3 -. AtNRT1.5 appears to mediate nitrate efflux out of root cells and loading into the xylem for transport to the shoot , whereas AtNRT1.8 is involved in retrieving NO 3 -from the xylem parenchyma in the roots and shoots (Li et al 2010). Hence, both proteins cooperate to regulate long-distance nitrate transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both AtNRT1.5 and AtNRT1.8 were shown to be involved in long-distance transport of NO 3 -. AtNRT1.5 appears to mediate nitrate efflux out of root cells and loading into the xylem for transport to the shoot , whereas AtNRT1.8 is involved in retrieving NO 3 -from the xylem parenchyma in the roots and shoots (Li et al 2010). Hence, both proteins cooperate to regulate long-distance nitrate transport.…”
Section: Discussionmentioning
confidence: 99%
“…CsNRT1.5A function seems to be more complex and related to some adaptive response of plants to a variable external nitrate supply. In Arabidopsis NRT1.8 was shown to play a significant role in cadmium tolerance leading to nitrate retention in roots to enhance root nitrate assimilation under heavy metal stress (Li et al 2010). Hence, it was suggested that the coordinated regulation of NRT1.5 and NRT1.8 expression resulting in a reduction of nitrate translocation to shoots could be a common adaptive response of plant to a wide range of stresses (Li et al 2010;Gojon and Gaymard 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, nitrate transporters are expressed in all plant organs, allowing both long-distance transport of nitrate, and tailored delivery to cell types. Provision of nitrate to aerial organs first requires xylem loading by nitrate transporters (Lin et al 2008;Li et al 2010;Wang and Tsay 2011) and, therefore, identification of the transporters responsible may be assisted by knowledge of the tissue patterning of gene expression. MtNPF6.8 is expressed in shoots as well as in the pericycle region in roots (Pellizzaro et al 2014).…”
Section: Long-distance Nitrate Transportmentioning
confidence: 99%
“…Previous reports have shown that NRT1.8/NPF7.2 and NRT1.7/ NPF2.13 from the NRT1/PTR family play roles in NO 3 2 removal from the xylem and NO 3 2 loading into the phloem, respectively (Fan et al, 2009;Li et al, 2010). Thus, we examined the phenotypes of the nrt1.7 and nrt1.8 mutants under the LK condition.…”
Section: Nrt15 Function Does Not Depend On Skormentioning
confidence: 99%